2013
DOI: 10.3846/16111699.2011.642081
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Innovation Climate on Individual and Organisational Level Factors in Asia and Europe

Abstract: Organisation climate plays an important role for the innovation of an organisation. The purpose of this paper is to investigate connections between the innovation climate and individual and organisational level factors. Surveys were conducted among Japanese, Chinese, Estonian, Czech and Slovakian enterprises. Linear regression analysis was conducted. The results of an empirical study show that the innovation climate predicts differently some individual and organisational level factors in studied countries. Two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…This kind of climate requires an environment where creative and innovative approaches are supported and encouraged (Martins & Terblanche, 2003). It was recently found that the organization that has a strong innovative climate is likely to create new ideas, predicting individual innovation in the companies (Übius, Alas, & Elenurm, 2013). Martins and Terblanche (2003) highlight the importance to identify which should be these characteristics to improve innovation in the organizations because there is little agreement about them and the reported findings have been inconclusive.…”
Section: Organizational Climate For Innovation (Oci) and Innovative Wmentioning
confidence: 99%
“…This kind of climate requires an environment where creative and innovative approaches are supported and encouraged (Martins & Terblanche, 2003). It was recently found that the organization that has a strong innovative climate is likely to create new ideas, predicting individual innovation in the companies (Übius, Alas, & Elenurm, 2013). Martins and Terblanche (2003) highlight the importance to identify which should be these characteristics to improve innovation in the organizations because there is little agreement about them and the reported findings have been inconclusive.…”
Section: Organizational Climate For Innovation (Oci) and Innovative Wmentioning
confidence: 99%
“…Zmud () suggested that innovation emerges from the organizational climate in which employees find innovation to be desirable, as well as knowing their efforts at innovating will be supported with appropriate opportunities to create new value. In an organization that has a strong innovative climate, new ideas are received enthusiastically, even though it may be widely acknowledged that the majority of these ideas will not make it to market (Übius, Alas & Elenurm, ). As changes in the overall business environment have influenced new forms of organization design, there has been strong emphasis on teamwork and collaboration in the workplace (Anderson & West, ), which can have a favourable effect on innovation behaviours.…”
Section: Introduction: Innovation In Organizations – Processes and Tymentioning
confidence: 99%
“…Among these factors, innovative climate has been identified as crucial to organizational change and improvement (Nonaka & Takeuchi, 1995;Übius, Alas, & Elenurm, 2013). As such, we propose innovative climate as the third mechanism that may be associated with the likelihood to have energy relationships.…”
Section: Innovative Climate (Ic)mentioning
confidence: 99%